Medication Management of Anxiety and Depression by Primary Care Pediatrics Providers: A Retrospective Electronic Health Record Study - Lester, Talia R.; Bannett, Yair; Gardner, Rebecca M.; Feldman, Heidi M.; Huffman, Lynne C. (Frontiers in Pediatrics, 2022)
Objectives: To describe medication management of children diagnosed with anxiety and/or depression by primary care providers within a primary care network. Study Design/Methods: We performed a retrospective cross-sectional analysis of electronic health record (EHR) structured data from all children seen at least twice in a 4-year observation period within a network of primary care clinics in Northern California. For children who had visit diagnoses of anxiety, depression, anxiety+depression or symptoms characteristic of these conditions, we analyzed the rates and types of medications prescribed. A logistic regression model considered patient variables for the combined sample. Results: Of all patients 6-18 years old (N=59,484), 4.4% (n=2635) had a diagnosis of anxiety only, 2.4% (n=1433) depression only, and 1.2% (n=737) both anxiety and depression (anxiety+depression); 18% of children with anxiety and/or depression had comorbid ADHD. A total of 15.0% with anxiety only (n=357), 20.5% with depression only (n=285), and 47.4% with anxiety+depression (n=343) were prescribed a psychoactive non-stimulant medication. For anxiety and depression only, the top three medications prescribed were sertraline, fluoxetine, and citalopram. For anxiety+depression, the top three medications prescribed were citalopram, sertraline, and escitalopram. Frequently prescribed medications also included benzodiazepines. Logistic regression modeling showed that the depression only and anxety+depression categories had increased likelihood of medication prescription. Older age and mental health comorbidities were independently associated with increased likelihood of medication prescription. Conclusions: In this network, approximately 8% of children carried a diagnosis of anxiety and/or depression. Medication choices generally aligned with current recommendations with the exception of use of benzodiazepines.